Spillover of Peste des Petits Ruminants Virus from Domestic to Wild Ruminants in the Serengeti Ecosystem, Tanzania - Mahapatra, Mana; Sayalel, Kuya; Muniraju, Murali; Eblate, Ernest; Fyumagwa, Robert; Shilinde, Ligge; Mdaki, Maulid; Keyyu, Julius; Parida, Satya; Kock, Richard (Emerging infectious diseases, 2015)
We tested wildlife inhabiting areas near domestic livestock, pastures, and water sources in the Ngorongoro district in the Serengeti ecosystem of northern Tanzania and found 63% seropositivity for peste des petits ruminants virus. Sequencing of the viral genome from sick sheep in the area confirmed lineage II virus circulation.